CORRELATION COEFFICIENT STUDY OF PHYSICO-CHEMICAL PARAMETERS OF KHANAPUR WATER RESERVOIR, DIST. OSMANABAD MAHARASHTRA, INDIA - JADHAV, SWATI; HUMBE, ATUL; PADWAL, NITIN (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Present work deals with the assessment of physico chemical parameters of water samples of Khanapur Water reservoir at different selected sites in the year July 2019 - June 2020. The water sample were collected were analyzed, as per standard methods parameters such as Temperature, pH, EC, Turbidity were measured in situ. Correlation coefficients were calculated between different pairs of parameters to identify the positive and negatively correlated parameters was applied for checking significance. Correlation coefficient showed high significant positive and negative relationship (p< 0.01 level) and also show significant positive and negative relationship (p<0.05 level) in different pairs of parameters.